Treatment of aggressive lymphoma (Hematology Meeting Reports, 2009)
Treatment of aggressive B cell lymphomas is rapidly evolving with the introduction of monoclonal antibodies in association with chemotherapy. Reappraisal of the progress made with chemotherapy is important to decide which part of the past strategies with intensive treatment should still be used. Long term results of the first studies with R-CHOP, identify patients more likely to respond to treatment with Bcl2 over expression and low-intermediate risk factors. However, poor prognosis patients still exist and remain a challenge for investigations. Improving the use of chemotherapy and monoclonal antibodies will be the goals of the design of prospective studies.